The Masculine Mountie: The Royal Canadian Mounted Police as a Male Institution, 1914-1939 - Hewitt, Steve (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1996)
Abstract1914 to 1939 was a very important period in the history of the Royal Canadian Mounted Police (RCMP). The Force found its very existence threatened. It also was transformed as it lost and then regained a role at the provincial level of policing, found itself amalgamated with the Dominion Police in 1920, and experienced widely fluctuating personnel levels throughout the period. Finally, it took on a security/intelligence role that would last until 1984. “The Masculine Mountie” looks at the Mounted Police in this era. Specifically the paper uses gender and ethnic analysis to explore the values and characteristics of the RCMP and how they affected the work it performed. Who Mounties were leads directly into what they did. These two aspects are very related, a reality that is too often ignored in much of the writing about Canada's national police force. Finally, the paper connects these various threads in an effort to deal with the important question of why the RCMP survived and prospered in its era of great uncertainty.